Factors contributing to attending Traditional Birth attendants among Pregnant Mothers aged 18-45 Years in Bubaare Sub County, Mbarara District. A Cross-sectional Study. - Rutindangyezi, Malic; Nakasolo, Sania (Student's Journal of Health Research Africa, 2022)
Background: The purpose of the study is to determine factors contributing to attending traditional birth attendants among pregnant mothers aged 18-45 years in the Bubaare sub-county, Mbarara district. Methodology: The study design was descriptive and cross-sectional and the researcher employed a simple random sampling technique to get 50 respondents. Data was collected using semi-structured questionnaires. Results: Most (55%) of the respondents were encouraged by the community to deliver at a hospital, and the majority (60%) were not accompanied by their husbands during delivery, most (48%) of the respondent's husbands decided the place of delivery, most(77%) of respondents had cultural beliefs and the majority (70%) of the respondents believed in religious affairs. (68%) of the respondents used skilled birth attendants, most (47%) of the respondents were not allowed by partners to deliver in hospitals, most (60%) 0f respondents attended antenatal, most (62%) of the respondents attended antenatal once, most (60%) attended antenatal in their second trimester, most (69%) of the respondents were wear of child delivery from the hospital and most (60%) of the respondents did prefer hospital delivery due to long waiting hours at the facility. Conclusion: Communally services offered by TBAS are giving advice both before and after delivery about nutrition, individually partners influencing mothers' place of delivery, and health-wise distance to the facility was long limiting their delivery from hospitals. Recommendation: The recommends that TBAS should be trained and equipped with modern medical knowledge by the government to easily handle uncomplicated deliveries.